Governmental activity and private capital investment - Ingrid Ott; Susanne Soretz (Universität Lüneburg, Institut für Volkswirtschaftslehre, 2006)
We analyze within a dynamic model how firms decide on capital investment if the accompanying adjustment costs are a function of governmental activity. The government provides a public input and decides on the degree of rivalry. The productive public input enhances private capital productivity and reduces adjustment costs. We derive the equilibrium in which capital and investment ratio are both constant, carry out comparative dynamic analysis and discuss the model's policy implications.
Keywords: D21; H40; H54; O16; 330; Investition; Infrastrukturinvestition; Bottleneck; Anpassungskosten; Dynamisches Gleichgewicht; Theorie